Analisis Praktik Pembiasaan untuk Menumbuhkan Kebiasaan Positif Siswa di SMA Khatolik Caritas Maumere - Theresia Bunga Karlince; Elisabeth Timu; Fitriah Fitriah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aims to analyze efforts to implement positive habits with refraction practices at the SMA Caritas Chatolic. This school always applies the 3s culture (smile, greet, greet) to create a supportive and harmonious environment. Every morning we always pray together in the Maria cave which is right in front of the school to increase students' religious and spiritual values. Apart from that, every Saturday there is always community service to instill the spirit of mutual cooperation, as well as various extracurriculars, such as fighting, cricket and futsal. This was developed to shape students' skills and character. Even though this program is running well, there are also challenges faced, such as the lack of involvement of some students in school activities which is still a concern.